The "Indian" Monotheism. - Basu, Anustup (Boundary 2)
This essay is a wide-ranging inquiry into an early and consistent monotheistic impulse in Hindu nationalist discourses and identity formation since the late nineteenth century. It argues that the consolidation of a pan-Indian Hindu demographic and religious identity, cutting across a formidable and awry range of local devotional traditions and deities, entailed a form of modernist transcoding that was tendentially monotheistic. It would seem that a singular Hindu national imagination could be secured only when such myriad energies—differing vastly in terms of caste, class, region, local cosmologies, linguistic, and cultural formations—could be harnessed into a monotheistic edifice of faith. Only then could that singular faith be parlayed into nationalist feeling for one Hindu nation. The aspired-for Hindu monotheism would then not just yield a Hindu nation in the world but would also be equipped to synchronize with other monothematic mantras of modernity like scientific progress, democracy, or techno-financial development. The essay visits some nodal moments of this historical narrative—the coming into being of a Hindu "tradition" under the auspices of colonial Indology, Rammohun Roy's defense of Vedic monotheism, Bankimchandra Chattopadhyay's efforts at using modern disciplinary knowledge (history, philosophy, science, aesthetics) to formulate a system of Hindu ethics and to establish Krishna as a singular messianic figure like Christ or Buddha, or a later moment in Savarkar's time, when the theological question had to be sidelined altogether in favor of a more pragmatic Hindu cultural nationalism. The essay visits some cardinal points of tension and historical consequences in the fragmented, still unfolding story of this monotheistic drive.